Treatment-induced neuropathy of diabetes overlapping with chronic inflammatory demyelinating polyradiculoneuropathy after rapid glycemic correction: a case report - Hu, Yonglu; Dong, Bingzi; Liu, Lijun; Deng, Yujie; Han, Runhong; Li, Chengqian (Frontiers in Endocrinology, 2025)
Treatment-induced neuropathy of diabetes (TIND) often presents with acute-onset neurological symptoms and is frequently underdiagnosed in clinical practice, typically occurring after rapid correction of hyperglycemia. Its coexistence with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) has rarely been reported. As both conditions involve peripheral neuropathy and inflammation, they may share common underlying mechanisms. We report the case of a 26-year-old male patient with type 1 diabetes mellitus (T1DM) who developed TIND followed by CIDP. The patient received insulin pump therapy for glycemic control, along with oral analgesics, including gabapentin and carbamazepine. Targeted treatment for CIDP with methylprednisolone was initiated, leading to improvement in neurological symptoms. Due to persistent severe perineal pain, the patient also underwent interventional pain procedures, including perineal nerve pulsed radiofrequency therapy. Additionally, we review the literature on the pathophysiological mechanisms of TIND and discuss its potential relationship with CIDP, aiming to provide clinical insights that may assist in early recognition and diagnosis. To date, cases of coexisting TIND and CIDP in a single patient have rarely been reported in the literature.